O processo variável do abaixamento das vogais médias pretônicas no município de Monte Carmelo-MG - Rezende, Fernanda Alvarenga (2013)
The main objective of this study was to describe and analyze the lowering of pre-stressed mid vowels /e/ and /o/ in the dialect of Monte Carmelo-MG, in words like: n[ɛ]gócio for n/e/gócio and m[ɔ]rar for m/o/rar. This research was methodologically guided by the precepts of Variation Theory, proposed by Labov (1972). As this author suggests the recorded interviews as a good way to get a large amount of reliable data, we interviewed 24 people born in Monte Carmelo-MG and they were randomly selected according to the three extra linguistic variables defined for this study: gender (male and female), age (between 15 and 25 years old, between 26 and 49 years old and above 49 years old) and educational level (between 0 and 11 years of study and over). The linguistic variables considered in the analysis were: mode of articulation of the preceding context; point of articulation of the preceding context; mode of articulation of the following context; point of articulation of the following context; vowel height of the stressed syllable; vowel articulatory position of the stressed syllable; vowel quality of the stressed syllable; distance of pre-stressed mid vowel from stressed syllable; distance of pre-stressed mid vowel from the beginning of the word; type of vowel of the pre-stressed syllable and lexical item. After the orthographic transcription of all interviews, we selected and encoded all data related to the maintenance and lowering of the mid-high vowels /e/ and /o/ in the pre-stressed position to finally submitting them to the package of programs GoldVarb X. The rounds in the statistical program resulted in a total of 6.963 productions of /e/ and /o/ in the pre-stressed syllable, with 635 being the realization of [ɛ] and 402 with the realization of [ɔ] in that syllable position. Our results showed that, in Monte Carmelo-MG, the lowering of vowels /e/ and /o/, in the pre-stressed position, occurs primarily due to a process of assimilation of feature, resulting in the vowel harmony by the feature [+ open 3]. This feature is triggered by mid-high vowel /ɛ/ and /ɔ/ of the stressed syllable. Aiming to represent from a theoretical model the prevalent rule for variation of mid vowels, we based on phonological theory of the Geometry of Features, proposed by Clements (1985, 1989, 1991), which allows us to visualize the process occurring through the spreading or assimilation of features of a segment by a next segment.